2009
DOI: 10.1590/s1678-77572009000100010
|View full text |Cite
|
Sign up to set email alerts
|

CAD/CAM Zirconia vs. slip-cast glass-infiltrated Alumina/Zirconia all-ceramic crowns: 2-year results of a randomized controlled clinical trial

Abstract: The aim of this randomized controlled clinical trial was to compare the early clinical outcome of slip-cast glass-infiltrated Alumina/Zirconia and CAD/CAM Zirconia all-ceramic crowns. A total of 30 InCeram® Zirconia and Cercon® Zirconia crowns were fabricated and cemented with a glass ionomer cement in 20 patients. At baseline, 6-month, 1-year, and 2-year recall appointments, Californian Dental Association (CDA) quality evaluation system was used to evaluate the prosthetic replacements, and plaque and gingival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
76
2
7

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 18 publications
(22 reference statements)
7
76
2
7
Order By: Relevance
“…According to these studies, fractures of the veneer requiring replacement of the crowns were few and ranged between 0 and 1.9 % at 2-5 years. Only one fracture of the zirconia core was reported [12]. Current clinical studies on zirconia-based multiunit FDPs [18][19][20][21] confirm previous systematic reviews [4][5][6]: chipping of the veneering ceramic was a frequent complication, whereas fractures of the core only seldom occurred.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…According to these studies, fractures of the veneer requiring replacement of the crowns were few and ranged between 0 and 1.9 % at 2-5 years. Only one fracture of the zirconia core was reported [12]. Current clinical studies on zirconia-based multiunit FDPs [18][19][20][21] confirm previous systematic reviews [4][5][6]: chipping of the veneering ceramic was a frequent complication, whereas fractures of the core only seldom occurred.…”
Section: Introductionsupporting
confidence: 61%
“…Clinical data on zirconia-based SCs are scarce. In short-term studies, failure rates ranged from 0 to 11.2 % at 2-5 years [12][13][14][15][16][17]. However, the rates of "biological" and "other complications" were not specified relative to "fractures of the ceramic" [13,17].…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-two studies were finally included in the qualitative synthesis. 26,27,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] Inter-reviewer agreement during the second review phase ranged from 'substantial agreement' to 'almost perfect agreement' (kappa: 0.715 -0.933) ( Table 2). The flowchart of the results and the review process according to the PRISMA statement is provided in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Although zirconia fixed partial dentures have been most commonly investigated (Tinschert et al, 2005;Vult von Steyern et al, 2005;Sailer et al, 2006), the sparse information regarding single crowns has shown similar results concerning the principal failure mode, which involved fractures within the veneering ceramic (Cehreli et al, 2009;Ortorp et al, 2009;Groten and Huttig, 2010). A method to reproduce these failure modes in the laboratory has been developed using mouth-motion fatiguetesting in water (Coelho et al, 2009a,b;Silva et al, 2010), where mechanical testing has confirmed the susceptibility of zirconia crowns to porcelain veneer failure.…”
Section: Introduction Cmentioning
confidence: 99%